Armed with Cameras and Guns: A Decolonial Reading of Patagonia, Ethnological Archives, and Nation in the First Peronismo - Vezub, Julio Esteban (2021)
Vezub and De Oto parse out the double discourses present in anthropological photography in twentieth-century Argentine nationhood. Ethnography thus becomes a powerful tool to create the national archive, reaffirming the coloniality of power, by way of representation and through the placement of indigenous bodies in relation to ethnographers who, engaged in processes of internal colonialism, behaved like earlier colonial explorers. This article presents a rupture in the dominant narrative as it interrupts myths of nationhood and integration of the Tehuelches people with a counternarrative that presents decolonial possibilities within the photographic archive. Maintaining the ambiguity in the discourse of Peronism itself, the authors emphasize that, while financing these ethnographic campaigns, Peronist leaders also supported emancipatory policies for the racialized working class. Los descamisados, a shirtless working-class and subaltern figure, emerges with Peronism, as a positive alternative to suit-wearing oligarchs in discourses of nationhood and nation-building. —Trans.